Structural, dielectric and ferroelectric properties of Nb-doped PZT thin films produced by oxide precursor method - Araújo, E. B. [UNESP]; Eiras, J. A. (My University, 2002)
Recently, was proposed a chemical method for preparation of ferroelectric thin films based on oxide precursors. In this work, PZT thin films were prepared to attest the viability of this method for cation-substitution. In this study, a small concentration of Nb (5 mol%) was selected as substitute of B-site in ABO 3 structure of PZT. Dielectric and ferroelectric properties of PZT films were studied as a function of cation-substitution. Results for Nb-PZT were compared with PZT films undoped. The values of dielectric constant, at typical 100 kHz frequency, were 358 and 137, for PZT and Nb-PZT films respectively. Remanent polarizations of these films were respectively 7.33 μ C/cm 2 and 13.3 μ C/cm 2 , while the measured coercive fields were 101 kV/cm and 93 kV/cm. As a result, changes on observed dielectric and ferroelectric values confirm the Nb substitution in PZT thin film produced by oxide precursor method. © 2002 Taylor & Francis.
Keywords: Ferroelectric; PZT; Thin films; Dielectric properties; Ferroelectricity; Lead compounds; Permittivity; Polarization; Substitution reactions; Cation-substitution; Oxide precursor method; Remanent polarizations